2022
DOI: 10.1155/2022/4093138
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Target and Multi-Channel Mechanism of Action for Jiawei Yinhuo Tang in the Treatment of Social Communication Disorders in Autism: Network Pharmacology and Molecular Docking Studies

Abstract: Background. Autism spectrum disorder (ASD) is a highly heterogeneous neurodevelopmental disorder with complex pathogenesis. Currently, the pathogenesis of ASD is not fully understood. Moreover, current treatments do not effectively alleviate the primary symptoms of ASD social disorder (SCDA). Jiawei Yinhuo Tang (JWYHT) is an improved version of the classic prescription Yinhuo Tang. Although this medication has been shown to improve social behavior in ASD patients, the mechanism by which it works remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Furthermore, the differentiation of osteoblasts was regulated by TNF- α , which was the earliest inflammatory mediator produced in response to oxidative stress and promoted the production of inflammatory cytokines to promote osteoblast apoptosis [ 39 , 40 ]. In addition, accumulating studies have revealed that the expressions of core targets, including Akt1, TNF- α , IL-6, and RELA, made the vital functions in regulating inflammatory response [ 41 , 42 ]. We have verified that QKF could regulate the key targets and PI3K/Akt/NF- κ B signaling pathway to explain the molecular mechanism of QKF treatment on DOP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the differentiation of osteoblasts was regulated by TNF- α , which was the earliest inflammatory mediator produced in response to oxidative stress and promoted the production of inflammatory cytokines to promote osteoblast apoptosis [ 39 , 40 ]. In addition, accumulating studies have revealed that the expressions of core targets, including Akt1, TNF- α , IL-6, and RELA, made the vital functions in regulating inflammatory response [ 41 , 42 ]. We have verified that QKF could regulate the key targets and PI3K/Akt/NF- κ B signaling pathway to explain the molecular mechanism of QKF treatment on DOP.…”
Section: Discussionmentioning
confidence: 99%
“…The RMSD reflects the movement of protein-ligand complexes during MDS. 34 The RMSD of the AKT1-tanshinone IIA backbone-backbone stabilized after 2 ns with a mean value of 0.234 ± 0.043 nm; the RMSD of the MMP9-luteolin backbone-backbone stabilized after 1 ns with a mean value of 0.194 ± 0.0189 nm. The RMSD of the AKT1-tanshinone IIA ligand-ligand was stable after 1 ns with a range of 0.032 ± 0.009 nm.…”
Section: Mdsmentioning
confidence: 95%